2002
DOI: 10.4049/jimmunol.169.2.787
|View full text |Cite
|
Sign up to set email alerts
|

B Cells Capturing Antigen Conjugated with CpG Oligodeoxynucleotides Induce Th1 Cells by Elaborating IL-12

Abstract: APCs initiate T cell-mediated immune responses against foreign Ags. Dendritic cells are professional APCs that play unique roles, including Ag-nonspecific capture, priming of naive T cells, and Th1 induction, whereas B cells generally lack these functions. In this study we uncovered novel aspects of murine B cells as APCs using CpG oligodeoxynucleotides (CpG) conjugated with an Ag. B cells served as efficient APCs independently of surface Igs. This characteristic was underlaid by the CpG-mediated Ag uptake and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 66 publications
2
37
0
Order By: Relevance
“…26 It has been shown that activated B cells produce IL-10 as well as IL-12p70, even under specific activation conditions. 3,7,19,27,28 In Fig. 3, B cells treated with CpG or LPS but not anti-CD40 produced IL-10 and IL-6 while LPS-matured DCs produced no IL-10 but did produce significantly greater amounts of IL-6 than activated B cells (P < 0Á05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 It has been shown that activated B cells produce IL-10 as well as IL-12p70, even under specific activation conditions. 3,7,19,27,28 In Fig. 3, B cells treated with CpG or LPS but not anti-CD40 produced IL-10 and IL-6 while LPS-matured DCs produced no IL-10 but did produce significantly greater amounts of IL-6 than activated B cells (P < 0Á05).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In spite of their practical advantages over DCs, including their abundance in peripheral blood, ease of expansion, simple preparation and homogeneity, activated B cells have been shown to be less efficient stimulators of T cells than DCs. Croft et al 10 demonstrated that DCs were far superior to activated B cells in inducing proliferation and interleukin-2 (IL-2) production by naïve CD4 + T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies both in vitro and in vivo suggest that B cells are involved in Th2 responses (68 -70). However, B cells activated with oligodeoxynucleotide (CpG)-conjugated Ag promote Th1 differentiation from unprimed T cells (71). Effector B cell subsets that produce distinct sets of cytokines, named Be1 and Be2, have been demonstrated to facilitate Th1 and Th2 polarization, respectively (72).…”
Section: Cd8␣mentioning
confidence: 99%
“…After 1 day of culture, cells were fixed with 0.5% paraformaldehyde for 15 min at 37°C (22). After extensive washing, cells (2 ϫ 10 5 cells/well) were cocultured with 3 ϫ 10 4 OT-1 cells in 96-well plates.…”
Section: In Vitro Stimulation Of Ot-1 Cellsmentioning
confidence: 99%